Reflecting Oil (Edition Angewandte, 2025)
Reflecting Oil presents innovative reflections on crude oil, one of the most important fossil fuels characterising modern life: On the one hand, oil functions as a fuel for unrestricted mobility and on the other, as a basis for shaping the material world, thus laying the foundation for a ubiquitous petroculture. Yet despite these profound repercussions on our existence, crude oil is a substance we rarely encounter directly with our senses. This lack of contact is logical in view of its specific properties (unusual odor, toxicity, etc.), but the question arises as to why this connection is not explicitly sought after in the sciences. Reflecting Oil is the result of different artistic research processes which entailed practical handling and holistic observation of the raw substance in the context of petroculture. This mode of research focusing on sensory perception—such as the differentiation of colors and smells, etc., and aesthetic and symbolic interpretation—provided findings on the levels of multi-sensory and practical knowledge. Drawing on a collaboration between art and science, such interdisciplinary investigations into crude oil as the basis of our petromodernity can be vital for the necessary shift towards sustainable energy cultures. A more comprehensive understanding and awareness of how oil and fossil fuels shape our lives can stimulate the necessary cultural, social, and technological transformations towards a sustainable future.